2017
DOI: 10.1002/sctm.16-0329
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 and MMP-14 Silencing Inhibits VEGFR2 Cleavage and Induces the Differentiation of Porcine Adipose-Derived Mesenchymal Stem Cells to Endothelial Cells

Abstract: The molecular mechanisms that control the ability of adipose‐derived mesenchymal stem cells (AMSCs) to remodel three‐dimensional extracellular matrix barriers during differentiation are not clearly understood. Herein, we studied the expression of matrix metalloproteinases (MMPs) during the differentiation of AMSCs to endothelial cells (ECs) in vitro. MSCs were isolated from porcine abdominal adipose tissue, and characterized by immunopositivity to CD44, CD90, CD105, and immunonegativity to CD14 and CD45. Plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…This observation was in comparison with MSCs treated with endothelial growth medium only. 143 In other work, the expression level of heme oxgenase 1 (HO-1 [HMOX1]) was genetically modified in MSCs and shown to increase MSCs resis-tance to cell death under oxidative stress conditions and enhance their anti-apoptotic properties. 144 Moreover, more MSCs overexpressing HO-1 survived following exposure to H 2 O 2 and hypoxia, indicating that HO-1 may shape the stress responsive and cytoprotective properties of MSCs.…”
Section: Genetic Modification Of Mscs (Gene Editing)mentioning
confidence: 99%
“…This observation was in comparison with MSCs treated with endothelial growth medium only. 143 In other work, the expression level of heme oxgenase 1 (HO-1 [HMOX1]) was genetically modified in MSCs and shown to increase MSCs resis-tance to cell death under oxidative stress conditions and enhance their anti-apoptotic properties. 144 Moreover, more MSCs overexpressing HO-1 survived following exposure to H 2 O 2 and hypoxia, indicating that HO-1 may shape the stress responsive and cytoprotective properties of MSCs.…”
Section: Genetic Modification Of Mscs (Gene Editing)mentioning
confidence: 99%
“…MSCs are capable of differentiating into several mesoderm lineages, including adipogenic, osteogenic, chondrogenic and myogenic lineages, depending on the multitude of stimuli and inhibitors present in the tissue microenvironment[ 50 ]. The micro-environment plays an important role in the activation or downregulation of transcription factors that regulate the expression of genes responsible for the induction and progression of tissue-specific differentiation[ 51 ]. MSCs can also generate neural cells in the ectodermal layer, and hepatic cells and pancreatic cells in the endodermal layer[ 52 ].…”
Section: Mesenchymal and Other Tissue-specific Stem Cells In Regeneramentioning
confidence: 99%
“…However, the molecular mechanism is still not completely described. Almalki et al [29] recently studied in vitro the expression of MMPs during the differentiation of AMSCs isolated from porcine abdominal AT to endothelial cells [29]. The authors demonstrated that the up-regulation of MMP-2 and MMP-14 has an inhibitory effect on the differentiation of AMSCs to endothelial cells; the silencing these MMPs inhibits the cleavage of the VEGF-receptor and stimulates the differentiation of AMSCs to endothelial cells and consequently the formation of endothelial tubes.…”
Section: The Role Of Mmps In Different Tissuesmentioning
confidence: 99%